Transformasi Manajemen Pendidikan Islam di Era Digital: Tantangan, Peluang, dan Arah Pengembangannya - Mulkan Hasibuan (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
This study employed a qualitative library research approach by critically reviewing relevant scholarly literature and recent studies on digital transformation in Islamic education management. The findings indicate that major challenges include unequal digital infrastructure, limited technological competencies among educational stakeholders, organizational resistance to change, and the need to maintain Islamic ethical values in digital environments. At the same time, digital transformation creates opportunities to improve administrative efficiency, support data-driven decision-making, expand access to educational resources, and strengthen institutional collaboration through digital platforms. The novelty of this study lies in its integrative analysis that positions digital transformation not merely as technological adoption but as a strategic management reform grounded in Islamic educational values. The study concludes that effective digital transformation requires visionary leadership, continuous professional development, sound digital governance, and the integration of technological innovation with Islamic ethical principles. These findings provide both conceptual and practical contributions for strengthening the sustainability and quality of Islamic education management in the digital era.